2021
DOI: 10.1088/1755-1315/648/1/012139
|View full text |Cite
|
Sign up to set email alerts
|

The potency of sub-micron dolomite in reducing yellow latex contamination in mangosteen fruits

Abstract: In Indonesia, mangosteen has high potency as an export commodity, but the qualityof the fruit is low. Yellow latex contamination is the the main problem in mangosteen fruit quality. The purpose of this research was to study the potency of sub-micron dolomite to reduce yellow latex contamination. This research was conducted in Guguk district, Lima Puluh Kota regency, West Sumatera province, Indonesia, from June 2016 until March 2017. In this experiment, the productive mangosteen trees (12 years) were used as pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…This condition occurred in calcareous soil. As [24] showed that application of submicron dolomite more than 120g/tree decreased Mn concentration in mangosteen leaves.…”
Section: Soil Chemical Propertiesmentioning
confidence: 93%
“…This condition occurred in calcareous soil. As [24] showed that application of submicron dolomite more than 120g/tree decreased Mn concentration in mangosteen leaves.…”
Section: Soil Chemical Propertiesmentioning
confidence: 93%
“…Namun, proses tersebut belum sesuai dengan standar GAP. Teknik pengabdian yang dilakukan antara lain: Teknik pemberian materi mengenai teknik penyimpanan 25 o C/70-75% R.H dan 13°C/90-95% RH tanpa menggunakan pelapis (de Castro et al, 2012), (Martias et al, 2021), (Indiarto, 2020).. Buah-buahan dikemas dalam baki polystyrene (EPS) yang diperluas (5 buah/nampan). Lima perawatan dilakukan pada 13°C/90-95% RH: penerapan lapisan lilin carnauba, lesitin + Lapisan CMC (selulosa karboksitil), lapisan film LDPE (polietilen kepadatan rendah) 50 μm, 13 PVC μm (Polivinil klorida), dan sampel non-dilapisi (perawatan kontrol 13°C).…”
Section: Bahan Dan Metodeunclassified